Defect width as a percentage of transverse abdominal diameter: An index to predict the requirement for component separation in incisional hernia repair - Ping Wang; Zicheng Guo; Hua Jin; Zhun Chen; Qingqing Li; Yonggang Huang (Heliyon)
Purpose: Preoperative decision making prior to incisional hernia repair brings benefits but also presents challenges. Defect width (DW) is the key index in hernia staging but does not precisely indicate the requirement for component separation (CS). DW as a percentage of transverse abdominal diameter (TAD) determined by CT imaging was investigated for its capacity to indicate the necessity of CS for successful defect closure under physiological tension. Methods: A total of 116 patients treated for incisional hernia by surgery between April 1st, 2015 and September 30th, 2020 were enrolled and clinical data retrospectively analyzed. All hernias were repaired with defect closure and mesh reinforcement. 82 patients received Rives-Stoppa repair (RS group) and 34 Rives-Stoppa repair with CS (CS group). Preoperative CT images were reviewed to measure maximum DW and TAD at umbilical level and the DW/TAD percentage (DTP) calculated. Accuracies of DW and DTP in predicting necessity of CS were compared through statistical analysis. Results: Mean RS DW was 59.41 ± 18.70 mm and CS DW 105.76 ± 13.47 mm (p = 0.000). Mean RS DW/TAD percentage was 21.25 ± 6.48 and CS DW/TAD 38.56 ± 6.26 (p < 0.05). Area under the curve (AUC) for receiver operating characteristic (ROC) curves gave values of 0.798 for DW and 0.825 for DTP (p < 0.05). Conclusion: DTP is a reliable index with greater accuracy than DW for prediction of the necessity of CS in incisional hernia repair.